Biomineralization Grouting for Beach Sand Cemented with MICP - Daryono, Lutfian Rusdi; Aoki, Sonoko; Kano, Masanao; Miyanaga, Mimori; Nakashima, Kazunori; Kawasaki, Satoru (Department of Civil and Environmental Engineering, Faculty of Engineering, Universitas Gadjah Mada, 2024)
Microbial-induced carbonate precipitation (MICP) is an environmentally friendly approach that relies on the production of calcium carbonate by microorganisms to construct or reinforce coastal structures. In order to address the disadvantages of current coastal countermeasures techniques, MICP is a cost-effective solution that can be used to repair and restore coastal habitats damaged by human activities. The resulting structures formed through MICP are strong and durable, providing long-term protection against erosion and flooding caused by storms or rising sea levels. Biominerals, including calcium carbonate or calcium phosphate, are used to create complex composites with organic molecules by combining the strength of inorganic materials with the versatility and biocompatibility of organic macromolecules. It is of the utmost importance to investigatethe functionality of MICP and scale up its deployment in various fields in order to thoroughly assess the instrument’s application. Coastal erosion has been a severe concern in archipelagic countries. Therefore, this study explored the Miyazaki coast in Japan and the Yogyakarta coastline in Indonesia to minimize coastal erosion using MICP. The bacteria found in Miyazaki (Sporosarcina species) and the Yogyakarta coast (Pseudoalteromonas tetradonis) were used in the experiment. As a result, the sample treated with a gradual injection of the cementation solution achieved about 6 MPa UCS after 21 days of treatment. The objective were investigated the potential biotreatment with original sand materials and to evaluate the long-term durability under saturated conditions. For these purposes, the MICP-treated sand columns were subjected to series of compression tests and wet-drying (WD) durability analysis.